2005
DOI: 10.1068/p5142
|View full text |Cite
|
Sign up to set email alerts
|

Lines That Induce Phenomenal Transparency

Abstract: Three neighbouring opaque surfaces may appear split into two layers, one transparent and one opaque beneath, if an outline contour is drawn that encompasses two of them. The phenomenon was originally observed by Kanizsa [1955 Rivista di Psicologia 69 3-19; 1979 Organization in Vision: Essays on Gestalt Psychology (New York: Praeger)], for the case where an outline contour is drawn to encompass one of the two parts of a bicoloured figure and a portion of a background of lightest (or darkest) luminance. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…These junctions are disrupted when the knife is tilted (nullifying the effect), but preserved in other configurations that include observable reflections of background elements on the knife’s surface (see Figure 2A and C). The persistence of the transparent percept under these conditions is commensurate with observations made by Grieco and Roncato (2005), who demonstrated that specific contrast relationships between surfaces and outline contours support perceived transparency in flat images. Such critical stimulus features can even overcome inferences based on perceptual experience, as demonstrated by Kanisza’s paradoxical transparency images (reprinted in Gerbino, 2020), in which common opaque objects (including a knife!)…”
supporting
confidence: 86%
“…These junctions are disrupted when the knife is tilted (nullifying the effect), but preserved in other configurations that include observable reflections of background elements on the knife’s surface (see Figure 2A and C). The persistence of the transparent percept under these conditions is commensurate with observations made by Grieco and Roncato (2005), who demonstrated that specific contrast relationships between surfaces and outline contours support perceived transparency in flat images. Such critical stimulus features can even overcome inferences based on perceptual experience, as demonstrated by Kanisza’s paradoxical transparency images (reprinted in Gerbino, 2020), in which common opaque objects (including a knife!)…”
supporting
confidence: 86%
“…Visual lines may have different appearances and behave differently in perceptual space. They can appear simply as lines of their own on a background, or otherwise: boundaries between regions or surfaces [2][3][4][5][6]; line drawings [7][8][9][10][11][12]; edges (surface discontinuities) [10,13]; contours of flat figures (silhouettes) [10]; factors of visual organisation as in cases of contour rivalry [7,13]; generators and/or shape deformers (as in the Rubin vase [5]; and the Hering illusion [14]); inducers of phenomenal transparencies [15]; margins of forms in case of brightness contrasts with the adjacent areas [16]; gradients of depth [17]; textural elements (hatch line) [10]; marks or strokes (blobs of paint on canvas or paper), cracks or ruptures on surfaces [8,10], and so on. In some cases, such as marks, strokes, and cracks in surfaces, lines are very close in appearance to surfaces [18].…”
Section: Introduction 1visual Linesmentioning
confidence: 99%
“…Lines in pictorial space can be used to identify boundaries of areas of different colours or tones on a surface [ 8 ], to represent transparent planes [ 15 ], or the recognition of smooth objects following consistent ‘cognitive’ rules [ 22 ], etc. The variety of the great number of ways of appearance of lines cast doubt on their univocal representation in terms of axiomatic geometries.…”
Section: Introductionmentioning
confidence: 99%